Separate K-line contributions to fluorescence enhancement in electron probe microanalysis - Venosta, Lisandro Francisco (2013)
The behaviour of the fluorescence enhancement correction factor in electron probe microanalysis, as a function of incident electron energy and take-off angle, is assessed for different binary samples in a wide range of compositions. Monte Carlo simulations are employed to validate Reed's correction algorithm [S.J.B. Reed, Characteristic fluorescence corrections in electron-probe microanalysis, Br. J. Appl. Phys. 16 (1965) 913-926], by means of estimating the primary excited radiation volume and the volume corresponding to secondary fluorescence generation. Then, Reed's expression for the fluorescence enhancement has been modified to account for Kα and Kβ line contributions separately. It is clearly shown that in certain cases the assignment of all fluorescent contribution to the Kα lines may be inadequate, particularly when trace element analysis imposes an accurate determination of elemental concentrations.